Peran Mediasi Fintech dalam Meningkatkan Inklusi Keuangan Islam di Kalangan Generasi Z - Muhammad Naufal Majid (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2026)
This study aims to examine the influence of Shariah financial literacy on Shariah financial inclusion among Generation Z in Indonesia, using Fintech as a mediating variable. The urgency of this study is evident from the latest National Survey on Financial Literacy and Inclusion, which shows that the Shariah financial literacy index still lags far behind the conventional one. This study uses a quantitative research design with SEM-PLS analysis through SmartPLS 3. The data consists of Muslim Gen Z respondents in Indonesia, collected through purposive sampling. The results show that the Shariah financial literacy variable has a significant positive influence on Fintech and Shariah financial inclusion. The Fintech variable significantly enhances Shariah financial inclusion and serves as a mediating mechanism. The research model explains a substantial variation in the Shariah financial inclusion variable. The effect of Fintech proved stronger than the direct effect of Shariah financial literacy, and the indirect effect via bootstrapping was significant. This indicates Gen Z’s preference for digital financial accessibility and demonstrates that Shariah financial literacy requires a bridge for effective implementation. Enhancing Shariah financial inclusion requires integrating Shariah financial literacy with fintech innovation. Policymakers must prioritize digital financial infrastructure to reach Generation Z in Indonesia.